Small microplastic particles (S-MPPs) in sediments of mangrove ecosystem on the northern coast of the Persian Gulf. (September 2019) - Naji, Abolfazl; Nuri, Marzieh; Amiri, Parisa; Niyogi, Som
Abstract: We present a study of small microplastic particles (S-MPPs) in the sediments of mangrove ecosystem of Khor-e- Khoran, a Ramsar site in Iran. The spatial distribution of S-MPPs (<1 mm) in mangrove surface sediments were investigated, which provided new insights into the detection and composition of S-MPPs in the study area. S-MPPs were extracted via the air-induced overflow (AIO) extraction procedure, and then they were counted and categorized according to the particle shape, color and size. The mean number of S-MPPs at the five sampling sites ranged from 19.5 to 34.5 particles per kg dry sediment in Bandar Gelkan and Bandar Lengeh, respectively. In general, microfibres followed by fragments were the most common type of S-MPPs isolated in each site (>56% and ~35%, respectively). Sewage discharge is probably the main source of extracted fibres in almost all the sites. The observed S-MPPs were classified into two size groups (10–300 μm and 300–1000 μm). The majority of S-MPPs fell into the smallest size group which accounted for 70–97% of the total S-MPPs. Fourier transform infrared (FTIR) analysis of some subsamples showed that polyethylene (PE) was the most common recovered polymer. Some non-plastic particles were also isolated from plastic-like particles of suspected S-MPPs in the mangrove sediments using a Scanning Electron Microscope (FE-SEM). This study provided the first evidence of S-MPPs contamination in the mangroves of the Iranian coast of the Persian Gulf. Long-term studies are required to understand, monitor and prevent further microplastics pollution in the region. Highlights: The spatial of small microplastic particles (S-MPPs, <1 mm) in mangrove surface sediments was investigated for the first time in the Persian Gulf. Microfibres (>56%) with black color were the most common type of S-MPPs extracted in all sites The majority of the S-MPPs in the present study seemed to be secondary Microplastics